2019
DOI: 10.1371/journal.pone.0221060
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of human T-lymphotropic virus HTLV and its associated factors in donors of a blood bank of Medellín-Colombia, 2014-2018

Abstract: Background Research on HTLV in Colombia is limited; despite being an endemic country there are few studies on the magnitude of this infection. The aim of this study was to determine the seroprevalence of HTLV I/II and its associated factors in donors to a blood bank of Medellín Colombia, 2014–2018. Methods This is a cross-sectional study of 52,159 donors with a secondary information source. Seroprevalence of HTLV I/II was determined with its confidence interval and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
0
12
0
2
Order By: Relevance
“…A study that included all Colombian departments found an overall seropositivity of 0.3%, with most departments below 1% and Chocó being the only exception with 6.28% [239]. Similar studies from several blood banks from Medellin observed 0.06-0.176% positivity, mainly for HTLV-1 [243,244]. We also found two studies conducted on blood donors from Peru, Arequipa (0.9% HTLV-1 positive) and Abancay (3.4%, unknown subtype), and one in pregnant women from Lima (1.7% HTLV-1 positive) [253,254,256].…”
Section: Htlv Prevalence and Morbidity In Latin Americamentioning
confidence: 92%
“…A study that included all Colombian departments found an overall seropositivity of 0.3%, with most departments below 1% and Chocó being the only exception with 6.28% [239]. Similar studies from several blood banks from Medellin observed 0.06-0.176% positivity, mainly for HTLV-1 [243,244]. We also found two studies conducted on blood donors from Peru, Arequipa (0.9% HTLV-1 positive) and Abancay (3.4%, unknown subtype), and one in pregnant women from Lima (1.7% HTLV-1 positive) [253,254,256].…”
Section: Htlv Prevalence and Morbidity In Latin Americamentioning
confidence: 92%
“…In Peru, very few studies on HTLV-1 have been done in blood donors, showing a prevalence of around 0.9% [23]. Colombia shows a seroprevalence of HTLV-1/2 in the population of blood donors in Cali and Medellín of 0.24% and 0.176%-0.06%, respectively [24][25][26]. Also, a retrospective study analyzing screening and positivity for HTLV-1 and 2 data collected from 2001 to 2014 by Colombian blood banks, showed a cumulative reactivity of 0.30% [27].…”
Section: Resultsmentioning
confidence: 99%
“…En adición a lo anterior, investigaciones recientes se han ocupado de la morbilidad por htlv mediante el uso de diferentes pruebas; así, en la actualización de Iwanaga se incluyen estudios que emplearon aglutinación de partículas e inmunofluorescencia [26]; en el análisis que hacen de Cardona et al se estimó la ocurrencia de la infección mediante quimioluminiscencia y confirmación con Western blot (bandas rgp 46-i, GD21, p19, p24, p26, p28, p32, p36, p53) [27]; el grupo de Yousefi utilizó elisa [28] y Zhao et al se sirvieron de quimioluminiscencia y elisa [29], demostrando la alta diversidad de metodologías para la detección del virus.…”
Section: Discussionunclassified